The recommendations of the Land Transfer Commission of 1869, considered with especial reference to their applicability to transfer of land in Ireland - Urlin, R. Denny (Statistical and Social Inquiry Society of Ireland, 1874)
One of the last letters written by Richard Cobden contains these remarkable words: ?The Land Question has a wider bearing than has yet been given it in our public discussions; and it will not be seriously entertained by the people until it has been presented in its full significance?. If the lamented writer of these words had lived, and if his friend, Mr. Bright, had enjoyed health and vigour in the interval, the question of ?Free Trade in Land? would have made more rapid progress. It is unnecessary in this Society to explain the true meaning of a phrase, in which some persons profess to see foreshadowed the forcible depriving of one class of the community of some of their property. ?Free Trade in Land? simply means the removal of artificial obstructions to the sale and transfer of land?the rendering of transfers and transmissions of estates and charges as easy as possible?the approximation of dealings with land to dealings with government stock and railway shares.
Read before the Society, 16 December 1873
Keywords: Land transfer; Ninteenth century Ireland; Irish land question; Land reform; 314.15